Determining clinical biomarkers to predict long-term SARS-CoV-2 antibody response among COVID-19 patients in Bangladesh - Ahmed, Tasnuva; Hasan, S. M. Tafsir; Akter, Afroza; Tauheed, Imam; Akhtar, Marjahan; Rahman, Sadia Isfat Ara; Bhuiyan, Taufiqur Rahman; Ahmed, Tahmeed; Qadri, Firdausi; Chowdhury, Fahima (Frontiers in Medicine, 2023)
Background Information on antibody responses following SARS-CoV-2 infection, including the magnitude and duration of responses is limited. In this analysis we aimed to identify clinical biomarkers that can predict long-term antibody responses following natural SARS-CoV-2 infection. Methodology In a prospective study, we enrolled 100 COVID-19 patients between November 2020 to February 2021 and followed them for six months. Association of clinical laboratory parameters on enrollment, including lactate dehydrogenase (LDH), neutrophil-lymphocyte ratio (NLR), C-reactive protein (CRP), ferritin, procalcitonin (PCT), and D-dimer, with predicting the geometric mean (GM) concentration of SARS-CoV-2 receptor binding domain (RBD)-specific IgG antibody at 3 and 6-month post-infection was assessed in multivariable linear regression models. Result The mean ±SD age of patients in the cohort was 46.8±14 years, and 58.8% were males. Data from 68 patients at 3 months follow-up and 55 patients at 6 months follow-up were analyzed. Over 90% of patients were seropositive against RBD-specific IgG till 6 months post-infection. At 3 months, for any 10% increase in absolute lymphocyte count and NLR, there was a 6.28% (95% CI: 9.68, -2.77) decrease and 4.93% (95% CI: 2.43,7.50) increase, respectively, in GM of IgG concentration, while any 10% increase for LDH, CRP, ferritin, and procalcitonin was associated with a 10.63%, 2.87%, 2.54% and 3.11% increase in the GM of IgG concentration, respectively. Similarly, any 10% increase in LDH, CRP, and ferritin was associated with an 11.28%, 2.48%, and 3.0% increase in GM of IgG concentration at 6 months post-infection. Conclusion Several clinical biomarkers in the acute phase of SARS-CoV-2 infection are associated with enhanced IgG antibody response detectable after six months of disease onset. Measuring SARS-CoV-2 specific antibody responses requires improved techniques and not feasible in all settings. Baseline clinical biomarkers can be useful alternative as they can predict antibody response during convalescence period. Individuals with an increased level of NLR, CRP, LDH, Ferritin, and procalcitonin may benefit from the boosting effect of vaccines. Further analyses will determine if the biochemical parameters can predict RBD IgG antibody responses at later time points as well as the association of neutralizing antibody responses.